Antibacterial activity of asam gelugur (Garcinia atroviridis Griff) fruit extract against foodborne pathogens and its effect on microbial population in raw chicken - Khan, S.; Jaafar, A.H.; Rukayadi, Y. (Rynnye Lyan Resources, 2022)
Foodborne illness has a major impact on public health and is a major concern worldwide. The awareness about foodborne pathogens has increased among consumers because of their significant impact on public health. Moreover, research on safe natural plant products possessing antimicrobial activities against foodborne pathogens is vital because many consumers prefer natural compounds to synthetic ones. This study aimed to determine the antibacterial activity of Garcinia atroviridis Griff against foodborne pathogens and to evaluate the effect of the fruit extract in the microbial population in raw chicken meat at different concentrations and temperatures during storage. The antibacterial activity of G. atroviridis Griff was assessed using disc diffusion assay (DDA), minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC). The DDA results showed that the inhibition zone of the extract ranged from 6.50±0.50 to 11.00±0.00 mm. The minimum inhibitory concentrations (MIC) and minimum bactericidal concentrations (MBC) values of the extract ranged from 3.13 to 25.00 mg/mL and 6.25 to 25.00 mg/mL, respectively. G. atroviridis Griff maintained its antibacterial activity after being treated with different temperatures (4˚C, 25˚C, 60˚C and 80˚C) and various pH ranges (pH 3.0, 7.0, and 9.0). A 5.00% concentration of extract can reduce the microbial population in the raw chicken and maintain its microbiological quality with longer exposure within 21 days in storage conditions at chiller and freezer temperature. The findings showed that the asam gelugur extract might be used as a natural alternative preservative for reducing the microbial population in raw chicken and maintaining its microbiological quality during storage prior to cooking.